2021
DOI: 10.7251/ace2032059k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exports on Economic Growth in Bosnia and Hercegovina

Abstract: The importance of foreign trade and its impact on the economic growth have been the subject of numerous studies. There is no doubt that exports have a multiplier effect on the growth of gross domestic product, but economists are constantly interested in what the foreign trade multiplier is and why it is not higher. This paper deals with the analysis of foreign trade of Bosnia and Herzegovina, its geographical and production structure and concentration, as well as the causes of high and continuous deficits. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This conclusion is in accordance with results of Bojat, Kovačević and Kurušić (2021) who showed that economic openness, primarily through export-oriented policies, contributes to real GDP growth in the long term, while the impact of the share of imports in the domestic product is negatively correlated with GDP. Also, our results are in line with the results showed in Krajišnik et al (2020) who emphasized the importance of export structure for the economic growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This conclusion is in accordance with results of Bojat, Kovačević and Kurušić (2021) who showed that economic openness, primarily through export-oriented policies, contributes to real GDP growth in the long term, while the impact of the share of imports in the domestic product is negatively correlated with GDP. Also, our results are in line with the results showed in Krajišnik et al (2020) who emphasized the importance of export structure for the economic growth.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that economic openness, primarily through export-oriented policies, contributes to real GDP growth in the long term, while the impact of the share of imports in the domestic product is negatively correlated with GDP. Krajišnik, Gojković, Josipović and Popović (2020) investigated the impact of export structure on the economic growth of Bosnia and Herzegovina. This research showed that there is a bad structure of foreign trade production, and that it is necessary to improve the export performances of the economy of Bosnia and Herzegovina in order to reduce the foreign trade deficit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that economic openness, primarily through export-oriented policies, contributes to real GDP growth in the long term, while the impact of the share of imports in the domestic product is negatively correlated with GDP. Krajišnik et al (2020) investigated the impact of export structure on the economic growth of Bosnia and Herzegovina. This research showed that there is a bad structure of foreign trade production, and that it is necessary to improve the export performance of the economy of Bosnia and Herzegovina in order to reduce the foreign trade deficit.…”
Section: Literature Reviewmentioning
confidence: 99%